Secularization and the Subjectification of Belief: A Comparative Analysis of Max Weber and Mircea Eliade (Journal for the Study of Religion and History (JSRH), 2026)
In the field of religious studies, this paper revisits the important concept of secularization through the distinctive lenses of Max Weber and Mircea Eliade. Weber interprets secularization primarily as a historical process of rationalization and disenchantment, driven by the Protestant ethic and culminating in the world-mastering individual. In contrast, Eliade approaches it through the phenomenological dialectic of the sacred and the profane, viewing secularization as desacralization—a transformation rather than an eradication of the sacred, wherein the sacred retreats into the private realm or the unconscious. Despite these divergent methodologies—one socio-historical, the other phenomenological—both perspectives converge on a crucial point: the modern shift elevates the individual subject while relativizing or internalizing the cosmic and sacred frameworks that once encompassed the individual subject. This paper ultimately contends that the concept of secularization inadequately captures the core transformation in modern religious life. Rather than observing the mere privatization or decline of religion, we are witnessing the subjectification of belief: belief itself has become a matter of personal, reflexive appropriation, making the individual not merely a private believer, but the very subject and locus of belief.
Keywords: Secularization, Max Weber, Mircea Eliade, Subjectification